2022
DOI: 10.1002/advs.202103478
|View full text |Cite
|
Sign up to set email alerts
|

Designing Conductive‐Bridge Phase‐Change Memory to Enable Ultralow Programming Power

Abstract: Phase‐change material (PCM) devices are one of the most mature nonvolatile memories. However, their high power consumption remains a bottleneck problem limiting the data storage density. One may drastically reduce the programming power by patterning the PCM volume down to nanometer scale, but that route incurs a stiff penalty from the tremendous cost associated with the complex nanofabrication protocols required. Instead, here a materials solution to resolve this dilemma is offered. The authors work with memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 76 publications
2
24
0
Order By: Relevance
“…Filled circles indicate the experimentally obtained values in this study. Orange, blue, and green triangles indicate the plot for GST with GNR electrode, GST with CNT electrode, and conductive-bridge PCM. ,,, Blue and red open squares indicate the assumed operation energy in the product. (d) Cyclic endurance characteristic for the CrGT-based cell with 34 × 34 nm 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Filled circles indicate the experimentally obtained values in this study. Orange, blue, and green triangles indicate the plot for GST with GNR electrode, GST with CNT electrode, and conductive-bridge PCM. ,,, Blue and red open squares indicate the assumed operation energy in the product. (d) Cyclic endurance characteristic for the CrGT-based cell with 34 × 34 nm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…These findings clearly demonstrated that scaling down can significantly lower operation energy. Meanwhile, Yang et al recently showed that conductive-bridge PCM allows for the realization of extremely low operation energy even in large contact area . An approach to microstructure engineering by phase separation in conductive-bridge PCM is a new strategy to reduce operation energy by limiting the phase change region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In early 2022, we have designed a conductive-bridge phase-change memory (cbPCM) scheme [73] that combines the advantages of phase-change memory with filamentaryswitching in metal oxides. The essential idea is to minimize the active switching volume in conventional devices via phase separation.…”
Section: Introductionmentioning
confidence: 99%
“…4 Thus, the development of next-generation hardware has been an important area of research. [5][6][7] Among them, edge computing, utilizing the same device structure for rapid operations and data storage, is presenting itself as an excellent hardware design to tackle portable, data intensive applications. 8 The success of this approach depends on finding an excellent material platform capable of utilizing the full potential of this design.…”
Section: Introductionmentioning
confidence: 99%